Intrathoracic Sewing Needle in an Infant: An Unusual Case of Foreign Body Migration - Aggerwal, Neel; Vibhash, Chandra; Mishra, Pragya; Singh, Umesh B. (Lietuvos chirurgija, 2025)
Foreign body incidents are common in children, primarily involving ingestion or inhalation. However, transcutaneous migration of sharp objects like sewing needles into the thoracic cavity is exceptionally rare and potentially dangerous. We report a unique case of an intrathoracic sewing needle in a six-month-old infant, highlighting the diagnostic challenges, imaging findings, surgical approach, and the clinical outcome.